Crop capacity of corn hybrids depending on fertilizer rates and plant growth regulators on typical chernozems of the Left-Bank Forest-Steppe of Ukraine - Kalenska, S.; Svystunov, Yu.; Antal Т. (Scientific Progress & Innovations, 2025)
The article investigates the influence of the plant growth regulator Vitazym on the grain yield of corn hybrids, grown on two mineral fertilizer backgrounds on typical chernozems of the Left-Bank Forest-Steppe of Ukraine. The study is particularly relevant during the current military operations in Ukraine, as it seeks to reduce the cost of producing a product unit in the specific conditions of the growing regions, corn in particular. The research aims to study the influence of mineral fertilizer rates, the plant growth regulator Vitazym, the genetic potential of hybrid productivity, and weather conditions on the formation of corn grain yield. The effectiveness of the growth regulator Vitazym use on corn crops with an established optimal consumption rate of 1.0 l/ha in the 17th micro stage of plant growth according to the international BBCH scale on both mineral nutrition backgrounds (calculated for the planned yield (Background 1) and at 50 % of the calculated rate (Background 2) was substantiated. The studies determined the feasibility of introducing into production the most high-yielding hybrid Alekksandra, whose yield on average over 3 years was on the background of N120P90K90 kg a.s./ha for the best option 11.11 t/ha. And on the background of half calculated mineral fertilizers rate – N60P45K45 kg a.s./ha – 7.96 t/ha. The yield increases compared to the control option were 1.03 t/ha (10.22 %) and 0.93 t/ha (13.23 %), respectively. The yield of the Alekksandra hybrid in the most favorable 2016 year reached 11.90 t/ha. The practical significance of the obtained results lies in the development of recommendations aimed at increasing corn yields on the Left Bank Forest-Steppe of Ukraine through the integrated use of the high-yielding hybrid Alekksandra in production conditions. Use of growth regulator Vitazym at a rate of 1.0 l/ha in the 17th micro stage on the BBCH scale, corn cultivation with a calculated rate of fertilizer N120P90K90 kg a.s./ha for farms with a high level of resource provision and 50 % of mineral fertilizers rate – N60P45K45 kg a.s./ha for agricultural enterprises with medium and low levels of resource provision.